ANALYISIS OF THE EFFECT OF HEAT INLET VELOCITY ON CROSSFLOW FOR CHARACTERISTICS OF HEAT EXCHANGER SHELL AND TUBE - CENDY S.E TUPAMAHU; SEFNATH J.E SARWUNA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
The effect of the velocity (V) of the opposite flow and the temperature of the hot fluid inlet (Thi)on the characteristics of the shell and tube heat exchanger has been investigated with forcedconvection heat transfer and is applied to the design of oil coolers in aircraft, power generationunits and others. The test model is modified with hot fluid (oil) on the tube side and cold fluid(water) on the shell side. Experimental research was carried out with variations in velocity (V) =0.011 to 0.037m / s and hot fluid inlet temperature (Thi) = 363K to observe the characteristics ofthe heat exchanger along with increasing velocity (V) with a significant increasing gradient. Theresults of experimental research show that the increase in velocity (V) <0.037 m / s with the heatfluid intake temperature (Thi) 363 K, the heat exchanger characteristics increase, namely; Redhnumber is 23.29%, Nudh number is 34.52%, hi is 34.80%, Redc number is 28.36%, Nudc is36.95%, ho is 36.78%, U is 34.83%, q is 22.56% while efficiency (ɛ) is 71.79% at a speed (V)<0.024 m / s and a decrease in speed (V)> 0.024 m / s of 24.99